Protective effect of luteolin on acute lung injury in a rat model of sepsis - Celebi, Demet; Aydin, Pelin; Cinar, Irfan; Kutlu, Zerrin; Calik, Ilknur; Halici, Zekai; Bayraktutan, Zafer (Taylor & Francis Ltd, 2021)
We investigated the effects of luteolin (LUT) treatment on acute lung injury caused by cecal ligation and puncture (CLP) induced septic rats. We also investigated the relation between LUT and the cytokines, interleukin-10 (IL-10) and tumor necrosis factor-alpha (TNF-alpha). LUT was administered 1 h after CLP surgery. Administration of LUT reduced the glutathione level and superoxide dismutase activity in rat lung tissues. We also found significant reduction of malondialdehyde following LUT treatment. LUT administration also reduced TNF-alpha and IL-10 mRNA expression in lung tissue. Histopathologic investigation of lung tissue supported our biochemical and molecular findings. Administration of LUT ameliorated lung injury in CLP induced septic rats owing to its antioxidant and anti-inflammatory properties.
Keywords: Antioxidants; cecal ligation; IL-10; inflammation; luteolin; rat; sepsis; TNF-alpha